2021
DOI: 10.1016/j.jtos.2020.05.011
|View full text |Cite
|
Sign up to set email alerts
|

The eye as the discrete but defensible portal of coronavirus infection

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
10

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 101 publications
(107 reference statements)
0
60
0
10
Order By: Relevance
“…Some antiviral drugs can be more efficient by using zinc, and their abdominal discomfort will decrease [11]. Using a combination of CQ, zinc, and azithromycin as eye drops or spray/aerosol for eyelids and the ocular surface can prevent binding of SARS-CoV-2 to the eyes as one of the major pathways of importing the virus into the body [21]. Zinc ions in the structure of viral proteins also can be targeted, and some drugs like disulfiram have shown that it can release Zn 2+ from proteins of MERS-CoV and SARS-CoV and impair the proteins.…”
Section: Zincmentioning
confidence: 99%
“…Some antiviral drugs can be more efficient by using zinc, and their abdominal discomfort will decrease [11]. Using a combination of CQ, zinc, and azithromycin as eye drops or spray/aerosol for eyelids and the ocular surface can prevent binding of SARS-CoV-2 to the eyes as one of the major pathways of importing the virus into the body [21]. Zinc ions in the structure of viral proteins also can be targeted, and some drugs like disulfiram have shown that it can release Zn 2+ from proteins of MERS-CoV and SARS-CoV and impair the proteins.…”
Section: Zincmentioning
confidence: 99%
“…The combination of eyewear, medical masks, and frequent hygiene might play a synergistic role in preventing the spread of COVID-19. As suggested by the American Academy of Ophthalmology ( ) and the literature analysis [ 23 ], coronavirus can potentially spread through the eyes, and, thus, replacing contact lenses with glasses is encouraged There may be changing behaviors regarding going to medical institutes during the COVID-19 pandemic. However, from Figure 3 , it can be seen that there are still Herpes Simplex Virus (HSV) positive cases.…”
Section: Limitations and Other Assumptionsmentioning
confidence: 99%
“…The combination of eyewear, medical masks, and frequent hygiene might play a synergistic role in preventing the spread of COVID-19. As suggested by the American Academy of Ophthalmology ( ) and the literature analysis [ 23 ], coronavirus can potentially spread through the eyes, and, thus, replacing contact lenses with glasses is encouraged…”
Section: Limitations and Other Assumptionsmentioning
confidence: 99%
“…Virus entry and multiple signaling pathways (Ca 2+ release, cSrc, FAK, MAPK, and PI3K) occur upon Spike2-RGD-integrin interaction. 7 A "cytokine storm" is locally released (IL1β, IL6, IL8, TNFÎą, MIP1Îą, and VEGF), as first observed in patients showing fatal complications. 5 This specific panel was used to screen patients requiring prompt intervention to avoid acute respiratory distress syndrome (ARDS).…”
Section: Sars-cov2 Infection and Main Clinical Aspectsmentioning
confidence: 99%